2016
DOI: 10.1073/pnas.1523975113
|View full text |Cite
|
Sign up to set email alerts
|

Design of a small molecule against an oncogenic noncoding RNA

Abstract: The design of precision, preclinical therapeutics from sequence is difficult, but advances in this area, particularly those focused on rational design, could quickly transform the sequence of diseasecausing gene products into lead modalities. Herein, we describe the use of Inforna, a computational approach that enables the rational design of small molecules targeting RNA to quickly provide a potent modulator of oncogenic microRNA-96 (miR-96). We mined the secondary structure of primary microRNA-96 (pri-miR-96)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
193
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(194 citation statements)
references
References 38 publications
1
193
0
Order By: Relevance
“…Recently, small molecules that were designed to target the folded structure of the oncogenic noncoding RNA have shown significant antitumor effects in vivo by selectively modulating noncoding RNAs in cancer cells with no effects in normal cells (45). Additionally, locked nucleic acid (LNA) can serve as a therapeutic agent that specifically targets lncRNAs in vivo (46).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, small molecules that were designed to target the folded structure of the oncogenic noncoding RNA have shown significant antitumor effects in vivo by selectively modulating noncoding RNAs in cancer cells with no effects in normal cells (45). Additionally, locked nucleic acid (LNA) can serve as a therapeutic agent that specifically targets lncRNAs in vivo (46).…”
Section: Methodsmentioning
confidence: 99%
“…To identify small molecule leads, we utilized a strategy called Inforna, which identifies highly selective, privileged RNA-motif–small-molecule interactions 11, 12 . Inforna has successfully facilitated the design of potent small-molecule modulators of several RNA repeat expansion disorders 13, 14, 15 and cancer-related microRNAs 11, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…The compound also derepressed the effect of miR-96 on FOXO1 expression, enhancing protein amounts by 2-fold when 50 nM of Targaprimir-96 was used. (59) These studies were completed in both MDA-MB-231 (a cellular model of triple negative breast cancer) and 4175 (a breast cancer cell line that metastasizes to lung). (60) Additionally, the compound triggers apoptosis at 50 nM.…”
Section: In Vivo Activity Of Designer Compounds Targeting Oncogenic Nmentioning
confidence: 99%
“…These studies showed that Targaprimir-96 has a favorable pharmacokinetic and metabolism profile as the concentration in serum is greater than 1 μM at 48 h post-IP injection of either 2 or 7 mg/kg, 20-fold higher than the amount of compound needed to trigger apoptosis in cell culture. (59) Thus, the effect of Targaprimir-96 on tumor growth in vivo was assessed. IP injection of 10 mg/kg compound was well tolerated in animals and ablated tumor growth over the course of 21 days.…”
Section: In Vivo Activity Of Designer Compounds Targeting Oncogenic Nmentioning
confidence: 99%
See 1 more Smart Citation